RNAi specificity: how big of an issue is it? - Welch, Peter (Henry Stewart Talks, 2007)
siRNA design and use in mammalian cells, Avoiding off-target effects, Sense strand inactivation, Evading interferon/stress response, Smith-Waterman algorithm, Human, mouse and rat Stealth(tm) Select, Successful experimental design, Appropriate RNAi controls
Reviewed at 2016/10/13